Introgression from local cultivars is a driver of agricultural adaptation in Argentinian weedy rice - Presotto, Alejandro Daniel; Hernández, Fernando; Vercellino, Roman Boris; Kruger, Raúl; Fontana, Maria Laura; Ureta, Maria Soledad; Crepy, Maria Andrea; Auge, Gabriela; Caicedo, Ana (Wiley, 2024)
Weedy rice, a pervasive and troublesome weed found across the globe, has often evolved through fertilization of rice cultivars with little importance of crop-weed gene flow. In Argentina, weedy rice has been reported as an important constraint since the early 1970s, and, in the last few years, strains with herbicide-resistance are suspected to evolve. Despite their importance, the origin and genetic composition of Argentinian weedy rice as well its adaptation to agricultural environments has not been explored so far. To study this, we conducted genotyping-by-sequencing on samples of Argentinian weedy and cultivated rice and compared them with published data from weedy, cultivated and wild rice accessions distributed worldwide. In addition, we conducted a phenotypic characterization for weedy-related traits, a herbicide resistance screening and genotyped accessions for known mutations in the acetolactate synthase (ALS) gene, which confers herbicide resistance. Our results revealed large phenotypic variability in Argentinian weedy rice. Most strains were resistant to ALS-inhibiting herbicides with a high frequency of the ALS mutation (A122T) present in Argentinian rice cultivars. Argentinian cultivars belonged to the three major genetic groups of rice: japonica, indica and aus while weeds were mostly aus or aus-indica admixed, resembling weedy rice strains from the Southern Cone region. Phylogenetic analysis supports a single origin for aus-like South American weeds, likely as seed contaminants from the United States, and then admixture with local indica cultivars. Our findings demonstrate that crop to weed introgression can facilitate rapid adaptation to agriculture environments.